Bitcoin versus money: civil-law analysis of the concept (Ius Novum, 2019)
The article attempts to conduct a civil-law based analysis of bitcoin, which is the most representative example of the so-called cryptocurrencies. The unit, like money, fulfils the payment and exchange functions, becoming an alternative to traditional currencies. This circumstance justifies the need to consider whether bitcoin can be recognised as money. Therefore, it has been analysed against the background of the concept of money. The presented study has made it possible to assume that bitcoin constitutes private money. This, in turn, opens the possibility of assessing the manner of settling a liability expressed in a bitcoin unit, e.g. partially through the prism of the institutions typical of pecuniary payments. Such an approach is the only one that does not distort the essence of bitcoin, which was originally intended to be an alternative to legal money.
Keywords: bitcoin; money; currency; legal tender; cryptocurrency; legal money; private money